Estimating the Location of Scatterers Using Correlation of Scattered Rayleigh Waves - Harmankaya, U.; Kaslilar, A.; Wijk, K.; Wapenaar, C. P. A.; Draganov, D. S. (EAGE Publications BV, 2015)
Inspired by a technique called seismic interferometry, we estimate the location of scatterers in a scaled model, where many near-surface scatterers are present. We isolate the scattered wavefield and evaluate correlation of scattered waves at different receiver locations. The cross-correlation eliminates the travel path between a source and a scatterer, making the estimation of the scatterers’ locations dependent only on properties between the receivers and the scatterer. We illustrate the potential of this method by locating scatterers with ultrasonic laboratory measurements of scattered Rayleigh waves recorded on two parallel and orthogonal lines of receivers. As near-surface scatterers are potential weak zones and may pose risk for the environment, to mitigate geo and environmental hazards, this method can be an efficient alternative that can be used in detection of such structures.